Inhibition of NADPH Oxidase–Dependent Oxidative Stress in the Rostral Ventrolateral Medulla Mediates the Antihypertensive Effects of Acupuncture in Spontaneously Hypertensive Rats. Issue 2 (February 2018) - Wang, Xue-Rui; Yang, Jing-Wen; Ji, Cai-Shuo; Zeng, Xiang-Hong; Shi, Guang-Xia; Fisher, Marc; Liu, Cun-Zhi
Abstract : Oxidative stress in the rostral ventrolateral medulla (RVLM), where the sympathetic nervous control center is located, contributes to neural mechanisms of hypertension. Acupuncture was previously reported to favorably affect high blood pressure. However, little is known about the effect of acupuncture on oxidative stress–modulated mechanisms in hypertension. This study was designed to evaluate the hypothesis that acupuncture exerts an antihypertensive effect via ameliorating oxidative stress and the redox-sensitive pathway in the RVLM of spontaneously hypertensive rats. Two weeks of acupuncture reduced blood pressure and sympathetic nervous system activity in spontaneously hypertensive rats. Oxidative stress in the RVLM was alleviated by acupuncture, accompanied by a decrease in nicotinamide adenine dinucleotide phosphate oxidase activity and expression of its subunits. Acupuncture significantly altered the mitogen-activated protein kinases signaling pathway as assessed by pathway enrichment analysis in a gene chip assay. The phosphorylation of p38 mitogen-activated protein kinases and extracellular signal-regulated protein kinase 1/2, but not Jun N-terminal kinase, was downregulated by acupuncture. Microinjection bilaterally of the superoxide dismutase mimetic tempol, nicotinamide adenine dinucleotide phosphate oxidase inhibitor apocynin, or diphenyleneiodonium chloride into the RVLM mimicked the antihypertensive effect of acupuncture. In contrast, the nicotinamide adenine dinucleotide phosphate oxidase agonist tetrabromocinnamic acid abolished the beneficial effects of acupuncture. Furthermore, injection of capsaicin or surgical sectioning of the sciatic nerve abolished the antihypertensive effect of acupuncture. We conclude that acupuncture decreases high blood pressure and nicotinamide adenine dinucleotide phosphate oxidase in the RVLM of spontaneously hypertensive rats. The mitogen-activated protein kinases and the sciatic nerve are involved in the mechanism of acupuncture's amelioration of hypertension. Abstract : Supplemental Digital Content is available in the text.